Reset and rebuild for a better Philippines in the post-pandemic world - Adoracion M. Navarro; Margarita Debuque-Gonzales; Kris A. Francisco (Philippine Institute for Development Studies (PIDS), 2021)
Despite the continuing threat of the COVID-19 virus mutating, the pandemic will eventually end given widespread vaccination and virus suppression policies. Policymakers need to think ahead, assess scenarios of possible futures, and start to reset and rebuild toward a better Philippines in the post-pandemic environment. Owing to the many societal issues that the pandemic exposed and exacerbated, thinkers were compelled to scrutinize the current flaws in the capitalist system and how these can be fixed to ensure a more sustainable existence. The Great Reset agenda by the World Economic Forum is one example. This agenda is contextualized in the Philippine situation through three major strategies, namely: making businesses more ethical through stakeholder capitalism; pursuing a green and inclusive recovery; and maintaining a robust and healthy workforce. Policy insights and recommendations for each strategy include the following: for ethical business, enjoin companies to adopt universally recognized environmental, social and governance metrics, strengthen the country's competition framework, and create an equal environment for different businesses in similar industries; for green and inclusive recovery, make space for greening in the stimulus packages, create a pipeline of needed climate-smart infrastructure projects, identify and invest in green growth areas, support the calls for a green new deal in Southeast Asia, push Philippine concerns in the global debates on climate actions, and find alternatives in the face of carbon-related tradeoffs; and for a robust and healthy workforce, invest in reskilling and upskilling programs, revamp the social protection system, address the digital divide, and address the needs of the workers of the future.
Keywords: 330; COVID-19 pandemic; capitalism reset; stakeholder capitalism; green recovery; robust workforce